PENGARUH MOTIVASI, LINGKUNGAN KERJA, DAN IMBALAN TERHADAP PERFORMANCE - Tri Aminah; Yon Rizal; Tedi Rusman (FKIP Unila, 2015)
This research was motivated by low teacher performance. This research aimed to investigate whether there was an impact of work motivation, job environment and rewards toward certified teacher working performance at Senior High School in Kota Agung Subdistrict in 2014/2015 academic year. Method used this research was verificative description with expost facto approach and survey. Teacher population in this researcher were 125 teacher with number of respondent chosen based on Nomogram Harry King formula as many as 102 teachers. To test hypothesis 1, 2 and 3, the researcher used a simple regression and for hypothesis 4, the research used multiple linier regression. The result of analysis showeel that: (1) there has an impact of working motivation of teacher toward certified teacher performance, 2) there has an impact of job environment of teacher toward certified teacher performance, 3) there has an impact of rewards of teacher toward certified teacher performance, 4) there has an impact of working motivation, job environment, and rewards on certified teacher performance.Penelitian ini dilatarbelakangi oleh performance guru yang rendah. Penelitian ini bertujuan untuk mengethui apakah ada pengaruh motivasi kerja, lingkungan kerja dan imbalan terhadap performance pada guru sertifikasi SMA/MA Kecamatan Kota Agung Tahun Pelajaran 2014/2015. Metode dalam penelitian ini menggunakan deskriptif verivikatif dengan pendekatan Ex Post Facto dan Survey. Populasi penelitian ini berjumlah 125 orang guru dengan jumlah sampel berdasarkan rumus Nomogram Harry King sebanyak 102 orang guru. Untuk menguji hipotesis 1, 2 dan 3 menggunakan linier sederhana dan hipotesis 4 menggunakan regresi linier multipel. Hasil analisis menunjukan bahwa: (1) ada pengaruh motivasi terhadap performance guru, (2) ada pengaruh lingkungan kerja terhadap performance guru, (3) ada pengaruh imbalan terhadap performance guru, (4) ada pengaruh motivasi, lingkungan kerja, dan imbalan terhadap performance guru.Kata kunci: imbalan, lingkungan kerja, motivasi,performance